CIPROFLOXACIN HYDROCHLORIDE LOADED CHITOSAN NANOPARTICLE GEL: ADVANCED APPROACH FOR ENHANCING PERMEATION AND SUSTAINABILITY OF DRUG RELEASE - Dev, Dhruv; Bhardwaj, Urvashi; Prasad, D N (Asian Journal of Pharmaceutical Research and Development, 2018)
Transdermal drug delivery is one of the most reliable, appealing and effective technique which provides controlled and constant administration of drug. The aim of the study was to develop a gel form of nanoparticles loaded with ciprofloxacin hydrochloride in order to enhance the permeability of drug and for the release of drug over a period of 24 hrs. The nanoparticles were formulated by ionic gelation method using chitosan as a polymer and TPP as a cross linking agent. The compatibility of drug and polymer is studied by using FTIR spectroscopy and DSC method. There was no interaction observed by UV and FTIR study. The six different batches were prepared using different polymer and drug ratio. The fourth batch (N4) shows best results as compared to others which was used for further investigations. The formulation was then optimized for its particle size, zeta potential, morphology, drug content, drug entrapment efficiency, drug loading capacity and in-vitro permeation. TEM study reveals that the nanoparticles are spherical in shape and also confirms the size below 500nm. Drug release studies shows that nanoparticles could release drug for 24 hrs and follows zero order kinetics. From DSC analysis it was found that the drug was effectively encapsulated inside the chitosan nanoparticles. Finally, it was concluded that the penetration of ciprofloxacin hydrochloride was enhanced after loading it into chitosan nanoparticles and also the drug was release over 24 hrs. Keywords: Nanoparticles, Ciprofloxacin Hydrochloride, Chitosan, Carbopol 934